THE STUDENTS’ PERCEPTION TOWARDS THE EFFECTIVENESS OF SPEAKING FOR INTERMEDIATE SUBJECT TO SUPPORT THEIR SPEAKING SKILL OF ENGLISH DEPARTMENT STUDENTS IN MAKASSAR MUHAMMADIYAH UNIVERSITY - Inda Sari; Eny Syatriana; Eka Prabawati Rum (FKIP Unismuh Makassar, 2021)
This research is aimed to find out the Students’s Perception towards the Effectiveness of Speaking for Intermediate Subject to Support their Speaking Skill of English Department Students in Makassar Muhammadiyah University. This research was descriptive qualitative. The population were 20 students at the third semester. The instrument used observation and interview.As a result on the findings, the students gave the positive perception toward the implementation of speaking for intermediate subject to measure the effectiveness of speaking for intermediate subject to support their speaking skill. However, the students claimed that they have got many advantages during the implementation of speaking for intermediate subject. This research also found out that this strategy also needed to be improved by the lecturers in terms of giving instruction, observing the class and evaluating the implementation of speaking for intermediate subject.